Analisis Kemitraan dalam Pengembangan Ruang Terbuka Hijau (RTH) di Kota Semarang - Hidayani, Hanifatul; Warsono, Hardi (Journal of Public Policy and Management Review, 2017)
Green open space is very important to note. Green open space is needed in particular to balance the urban region urban air to keep them fresh. When the current green open spaces were available yet is developed and managed properly. Contributing factor is the lack of budget, lack of human resources, and a shortage of land for development. These problems can be overcome by establishing partnerships among the actors involved in the development of green open space. Therefore, this study aims to determine the role of each actor, determine the degree of partnership in the development of green open space, and efforts to be made in improving the partnership. Green open space is very important to note. Green open space is needed, especially in the region This study used a descriptive qualitative research motode documentation and interview as data collection techniques. The target in this research is the government, society, and the private sector participated in the development of green open space in the city of Semarang. The Partnership is a joint venture form of cooperation between two or more parties that aims to improve the ability of an organization in achieving its objectives. Based on the results of the overall study the problems encountered in relation to partnerships Semarang city government is not the implementation of partnerships with the private sector because of the difference between government and private interests. So far the government is trying to establish partnerships with the private sector.